Kuala Lumpur International Conference on Biomedical Engineering 2004, 2-4 September 2004, Hilton Petaling Jaya, Kuala Lumpur, Malaysia - Kuala Lumpur International Conference on Biomedical Engineering (2004 : Kuala Lumpur) (Kuala Lumpur : Faculty of Engineering University of Malaya, 2004)
42